The Blight and Burden of Inter caste Marriage: A Case of Bitalu - Biswakarma, Tilak (Nepal Journal of Sociology, 2025)
Bitalu is a demeaning label given by society that eventually turns into a surname. The Constitution of Nepal considers marriage a personal freedom, yet society regulates the formation of individual identity. Based on f ieldwork in the Karnali region of Nepal, this study focuses on non-Dalits who, because of their marriages to a Dalit woman, lost their ties to their parental caste and property and were eventually ostracized as Dalits by their families and society. Society regards those couples and their offspring as “Bitalu,” a derogatory label signifying the downward mobility of caste, treating them as impure. Thus, this paper sociologically scrutinizes the social and caste dynamics surrounding the term Bitalu, as well as the struggles and implications of the label affixed to these individuals, which affect them both socially and officially.